Protective role of MG53 against ischemia/reperfusion injury on multiple organs: A narrative review - Xu, Bowen; Wang, Chunxiao; Chen, Hongping; Zhang, Lihui; Gong, Lei; Zhong, Lin; Yang, Jun (Frontiers in Physiology, 2022)
Ischemia/reperfusion (I/R) injury is a common clinical problem after coronary angioplasty, cardiopulmonary resuscitation, and organ transplantation, which can lead to cell damage and death. Mitsugumin 53 (MG53), also known as Trim72, is a conservative member of the TRIM family and is highly expressed in mouse skeletal and cardiac muscle, with minimal amounts in humans. MG53 has been proven to be involved in repairing cell membrane damage. It has a protective effect on I/R injury in multiple oxygen-dependent organs, such as the heart, brain, lung, kidney, and liver. Recombinant human MG53 also plays a unique role in I/R, sepsis, and other aspects, which is expected to provide new ideas for related treatment. This article briefly reviews the pathophysiology of I/R injury and how MG53 mitigates multi-organ I/R injury.